Postawy rodziców i płeć psychologiczna a preferencja stylu kierowania - Tylka, Joanna (Acta Universitatis Lodziensis. Folia Psychologica, 2011)
The article is concerned with the subject of gender, parental attitudes and styles of people management. Theoretical grounds of the article refer to Gender Schema Theory worked out by S. L. Bem, Power/Interaction Model of Interpersonal Influence by B. Raven and Parental Attitudes Theory by M. Plopa. In the researches participated 122 executives (60 woman, 62 man) from southern Poland. The author used „Sex Role Inventory” A. Kuczyńskiej (IPP), Raven Interpersonal Influence Inventory, adapted by Z. Zaleski and Parental Attitude Scale of Plopa (KPR-Roc). There were found statistically significant associations between the paternal lability upbringing, overprotective maternal attitudes and directive style. Also was observed correlation between androgynous, mothers’ reasonable protection and democratic leadership style.